Some aspects of the unusual climatology of Storm Arwen (2021). (24th December 2021) - Smart, David; Lee, Simon H.; Graham, Edward
Abstract : Histogram of the difference in MSLP between 57.25°N, 7.25°W and 56.75°N, 2.25°W using hourly 0.25° ERA5 data for November–March in the period 1 January 1979 to 27 November 2021. The peak value during Storm Arwen (26/27 November 2021) is shown with a red arrow.